Gestión en la atención al público usuario y su influencia en el clima laboral de los colaboradores en la superintendencia nacional de registros públicos de la zona registral N° IX, Sede Lima - 2020 - Latorre Merino, Nelly Renée (2022)
The present research entitled "Management in the attention to the public user and its influence on the work environment of the collaborators in the National Superintendence of Public Registries of the Registry Zone No. IX, Lima-2020, was developed with the objective of determining if the attention to the public user influences the work environment. The research was denominated as a basic or pure research with a quantitative approach. A non-experimental, cross-sectional, descriptive design was considered and the survey technique was used to obtain data, and an instrument with 16 open questions was applied to a population made up of 175 collaborators of the Deputy Manager of the SUNARP Journal and Parts Desk. Finally, according to the results obtained, it is recommended that the management of customer service be managed and attended to by directors and collaborators following the procedures established by SUNARP and that it allows for an adequate and bearable working environment with the user.